APETx-Like Peptides from the Sea Anemone Heteractis crispa, Diverse in Their Effect on ASIC1a and ASIC3 Ion Channels - Kalina, Rimma S. (Toxins (Basel), 2020)
Currently, five peptide modulators of acid-sensing ion channels (ASICs) attributed to structural class 1b of sea anemone toxins have been described. The APETx2 toxin is the first and most potent ASIC3 inhibitor, so its homologs from sea anemones are known as the APETx-like peptides. We have discovered that two APETx-like peptides from the sea anemone Heteractis crispa, Hcr 1b-3 and Hcr 1b-4, demonstrate different effects on rASIC1a and rASIC3 currents. While Hcr 1b-3 inhibits both investigated ASIC subtypes with IC(50) 4.95 ± 0.19 μM for rASIC1a and 17 ± 5.8 μM for rASIC3, Hcr 1b-4 has been found to be the first potentiator of ASIC3, simultaneously inhibiting rASIC1a at similar concentrations: EC(50) 1.53 ± 0.07 μM and IC(50) 1.25 ± 0.04 μM. The closest homologs, APETx2, Hcr 1b-1, and Hcr 1b-2, previously demonstrated the ability to inhibit hASIC3 with IC(50) 63 nM, 5.5, and 15.9 μM, respectively, while Hcr 1b-2 also inhibited rASIC1a with IC(50) 4.8 ± 0.3 μM. Computer modeling allowed us to describe the peculiarities of Hcr 1b-2 and Hcr 1b-4 interfaces with the rASIC1a channel and the stabilization of the expanded acidic pocket resulting from peptides binding which traps the rASIC1a channel in the closed state.